2011
DOI: 10.1016/j.chembiol.2011.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Studies and Genetic Engineering of Pactamycin Analogs with Improved Selectivity toward Malarial Parasites

Abstract: Pactamycin, one of the most densely functionalized aminocyclitol antibiotics, has pronounced antibacterial, antitumor, antiviral, and antiplasmodial activities, but its development as a clinical drug was hampered by its broad cytotoxicity. Efforts to modulate the biological activity by structural modifications using synthetic organic chemistry have been difficult because of the complexity of its chemical structure. However, through extensive biosynthetic studies and genetic engineering, we were able to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 15 publications
3
92
0
1
Order By: Relevance
“…Our study highlights general principles for drug targeting and provides foundations for structure-based drug design. These structures will facilitate the development of next-generation antibiotics with reduced adverse effects and new therapeutics against infectious diseases, cancers and genetic disorders caused by premature termination codons [8][9][10][11][12] . High-resolution X-ray crystallography of the 80S ribosome opens a new area of investigation-a large number of ribosome inhibitors certainly remain to be discovered and analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study highlights general principles for drug targeting and provides foundations for structure-based drug design. These structures will facilitate the development of next-generation antibiotics with reduced adverse effects and new therapeutics against infectious diseases, cancers and genetic disorders caused by premature termination codons [8][9][10][11][12] . High-resolution X-ray crystallography of the 80S ribosome opens a new area of investigation-a large number of ribosome inhibitors certainly remain to be discovered and analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the eukaryotic ribosome is a major target for broad-spectrum and eukaryote-specific small-molecule inhibitors isolated from natural sources. Despite limited understanding of their molecular mechanism, eukaryote-specific ribosomal inhibitors are increasingly used in research and hold potential for new therapeutics against a wide range of infectious diseases, cancers and genetic disorders [8][9][10][11][12] .…”
mentioning
confidence: 99%
“…For instance pactamycin analogs have been generated via mutasynthetic approaches that have superior activities to the progenitor natural products [3, 50], glycovariants have been generated of a large number of natural products via enzymatic methods [31] and genetic knockouts [29]. …”
Section: How Can Genome Mining Be Leveraged?mentioning
confidence: 99%
“…Within the carbapenem family, the carpetimycins have three carbons in their C6 side chain (8), suggesting that a ThnK ortholog may be responsible for three methyl transfers. The natural product pactamycin has traditionally been compared with thienamycin, because both possess a hydroxyethyl side chain (18); however, a recent genetic knockout study has suggested that more than one enzyme takes part in attaching the ethyl group (20). Although sequential methylations appear not to occur by a single enzyme in pactamycin biosynthesis, other RS enzymes, including Swb9 (21) and PoyB or PoyC (22), in quinomycin and polytheonamide biosynthesis, respectively, have been implicated in multiple methylations of a single substrate chain.…”
Section: Significancementioning
confidence: 99%